2014
DOI: 10.1007/s11056-014-9438-4
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic stunting in bareroot Pinus banksiana seedlings is unrelated to colonization by mycorrhizal fungi

Abstract: Mosaic stunting, the occurrence of random patches of chlorotic seedlings with reduced shoot and diameter growth amidst more robust cohorts within bareroot nurseries, is classically associated with poor colonization by mycorrhizal fungi. We examined possible relationships among soil fertility, mycorrhizas, and random patches of mosaic stunting in bareroot Pinus banksiana Lamb. and suggest this paradigm is not universal. Stunted seedlings were distributed among healthy seedlings, occupied field space for 2-3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…These differences in glacial succession may have altered the genetic structure between jack pine found in central and northwest regions of Wisconsin, resulting in differences in seedling establishment. In addition to having poorer establishment, seedlings from the central seed lots in this study also had somewhat lower P and K concentrations than those reported in Potvin et al (2014) and Zhang et al (2015). The observed differences in seedling establishment between two different regions may be of interest to land managers when considering what seed to use for the restoration or management of jack pine barrens (if the land manager chooses to reseed after the prescribed fire).…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…These differences in glacial succession may have altered the genetic structure between jack pine found in central and northwest regions of Wisconsin, resulting in differences in seedling establishment. In addition to having poorer establishment, seedlings from the central seed lots in this study also had somewhat lower P and K concentrations than those reported in Potvin et al (2014) and Zhang et al (2015). The observed differences in seedling establishment between two different regions may be of interest to land managers when considering what seed to use for the restoration or management of jack pine barrens (if the land manager chooses to reseed after the prescribed fire).…”
Section: Discussioncontrasting
confidence: 64%
“…The 10-fold significant increase in available P and increase in NH 4 + -N in the laboratory-burn soil are consistent with the observation that high-temperature burns often generate ash that is rich in plant-available nutrients (Gray and Dighton, 2006;Bodí et al, 2014), and suggest an explanation for the observed increase in biomass in the laboratory-burned soils. A previous study of 2-yr-old jack pine seedling tissues found similar macronutrient and micronutrient values in healthy seedlings (Potvin et al, 2014), as did a study that analyzed 1-yr-old jack pine needles (Zhang et al, 2015). Thus, increased nutrient availability in the laboratory-burned O-horizon soil (in particular, P) may have resulted in greater nutrient uptake, as total amount of N, P, K, and other nutrients were higher in plants grown in laboratoryburned soils (due to increased total biomass, not greater concentration in the plant tissues [Table 3; Supplemental Table S3]).…”
Section: Jack Pine Produces More Biomass In Laboratory-burned Than Prmentioning
confidence: 78%
“…The "no S test" school believes foliar S tests are expensive and are not a worthwhile investment (Radwan and Brix 1986). They typically analyze foliage for all macronutrients except S (Madgwick 1964;McKee 1978;Mitchell et al 1980;Donald and Young 1982;Weetman and Wells 1990;Ericsson 1994;Hans 2013;Potvin et al 2014;Hachani et al 2020). Since foliar values corresponding to a S-deficiency in nonfertilized forests likely did not exist (Ingestad 1962), some saw no need to analyze foliage for S. Often S fertilization was assumed to not affect growth and nutrient uptake of seedlings (McKee 1978).…”
Section: Tissue Analysismentioning
confidence: 99%
“…When pine needles contain less than 5,000 μg g -1 Ca (Table 5), seedlings do not show toxicity symptoms. However, stunted seedlings may result when the concentration in foliage exceeds 6,500 μg g -1 Ca (van Lear and Smith 1972;Carter 1987;Landis 1988;Potvin et al 2014;Hachani et al 2020; Figure 4). Occasionally pine foliage exceeds 9,000 μg g -1 Ca (Table 5).…”
Section: Toxicitymentioning
confidence: 99%